2016
DOI: 10.1073/pnas.1525082113
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic framework for P4-P6 RNA reveals tertiary motif modularity and modulation of the folding preferred pathway

Abstract: The past decade has seen a wealth of 3D structural information about complex structured RNAs and identification of functional intermediates. Nevertheless, developing a complete and predictive understanding of the folding and function of these RNAs in biology will require connection of individual rate and equilibrium constants to structural changes that occur in individual folding steps and further relating these steps to the properties and behavior of isolated, simplified systems. To accomplish these goals we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 116 publications
7
35
0
Order By: Relevance
“…RNA tertiary formation, including that for formation of the TL/ TLR studied herein, is much slower than expected for diffusional collision; thus, there must be an additional step or steps preceding formation of the contact (21,27,48,49). Although in principle there might only be a need for two steps, tertiary contact rearrangement and alignment (diffusional collision), our results provide evidence for an additional step.…”
Section: Additional Tests Of the Potential Interplay Between Structurmentioning
confidence: 54%
See 4 more Smart Citations
“…RNA tertiary formation, including that for formation of the TL/ TLR studied herein, is much slower than expected for diffusional collision; thus, there must be an additional step or steps preceding formation of the contact (21,27,48,49). Although in principle there might only be a need for two steps, tertiary contact rearrangement and alignment (diffusional collision), our results provide evidence for an additional step.…”
Section: Additional Tests Of the Potential Interplay Between Structurmentioning
confidence: 54%
“…2B). Prior work demonstrated equivalent P4-P6 folding in Mg 2+ and Ba 2+ upon ablation of the MC, and independent studies demonstrated equal ion atmosphere occupancy for Mg 2+ and Ba 2+ surrounding a nucleic acid (21,45). Thus, we could change the electrostatic environment without complications from site-specific metal ion binding and formation of an additional tertiary contact ( (21) concentrations (Fig.…”
Section: +mentioning
confidence: 73%
See 3 more Smart Citations